Pengaruh Inovasi dan Kualitas Pelayanan terhadap Kepuasan Pelanggan dengan Citra Merek sebagai Variabel Intervening pada Pengguna Gojek di Kota Langsa - Annida Zahra; Riny Chandra; Maulana Rahman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of innovation and service quality on customer satisfaction with brand image as an intervening variable among Gojek users in the city of Langsa. This research is quantitative in nature, with the population being Gojek users in Langsa. The sampling technique used is purposive sampling, with a total of 100 respondents. The data were processed using SPSS for Windows version 25, and the analysis methods employed include classical assumption tests, path analysis, Sobel test, and hypothesis testing. The research findings indicate that: (1) innovation has no significant effect on customer satisfaction, (2) service quality has a significant effect on customer satisfaction, (3) innovation has a significant effect on brand image, (4) service quality has a significant effect on brand image, (5) brand image mediates the effect of innovation on customer satisfaction, (6) brand image mediates the effect of service quality on customer satisfaction, and (7) brand image has a significant effect on customer satisfaction.